THE REALIZATION OF GENDER ARGUMENTS OF INSTAGRAM PARTICIPANTS IN ARGUING ABOUT THE GOVERNOR ELECTION OF DKI JAKARTA 2017 - Tio Lasmidauli Lumban Gaol; Sri Minda Murni; Amrin Saragih (LINGUISTIK TERAPAN, 2019)
This research deals with the way of male and female participants of different social status in delivering argumentation on instagram. The purpose of this study was to explain the way male and female instagram participants in arguing on instagram, to describe how social status affects the languages of male and female instagram participants of different social status communicating in instagram and to explain the reason of male and female instagram participants use the language in the way they are. This research is conducted by applying qualitative descriptive research. The data in this study are nine arguments from male instagram participants who have higher status, lower and equal with female and nine arguments from female instagram participants who have higher status, lower and equal with male which has been selected in about two months. The findings indicate that male instagram participants tend to use conjunction, conditional and biconditional to convey their arguments in instagram, whereas female instagram participants tend to use the five types of argumentation ie negation, conjunction, dicjunction, conditional and biconditional in instagram. Male with higher social status argue in conditional with female and male of equal status, male of equal status argue conjunction with female and male of equal status, lower status male argue conjunction with male and female whose status is higher. Female with higher social status argue negation, disjunction and biconditional with female and male of lower status, female of equal status argue negation and conditional with equal status of female and male, male with status lower use conjunction and conditional with male and female whose status is higher. The reason why male and female instagram participants differ in their arguing is that instagram participants with high social status tend to be affected by their social status, they tend to use the argument to show that they are competitive and wise in arguing. While instagram participants who are of equal social status, tend to show solidarity and maintain communication. Participants with lower social status tend to be selfish by giving arguments that seem undeniable or responsive. Keywords: gender language, instagram participants, social status